Learning Curves of Macintosh Laryngoscope in Nurse Anesthetist Trainees Using Cumulative Sum Method - Panthila Rujirojindakul; Edward McNeil; Rongrong Rueangchira-urai; Niranuch Siripunt (Anesthesiology Research and Practice)
Background. Tracheal intubation is a potentially life-saving procedure. This skill is taught to many anesthetic healthcare professionals, including nurse anesthetists. Our goal was to evaluate the learning ability of nurse anesthetist trainees in their performance of orotracheal intubation with the Macintosh laryngoscope. Methods. Eleven nurse anesthetist trainees were enrolled in the study during the first three months of their training. All trainees attended formal lectures and practice sessions with manikins at least one time on performing successful tracheal intubation under supervision of anesthesiology staff. Learning curves for each nurse anesthetist trainee were constructed with the standard cumulative summation (cusum) methods. Results. Tracheal intubation was attempted on 388 patients. Three hundred and six patients (78.9%) were successfully intubated on the trainees’ first attempt and 17 patients (4.4%) on the second attempt. The mean ± SD number of orotracheal intubations per trainee was 35.5 ± 5.1 (range 30–47). Ten (90.9%) of 11 trainees crossed the 20% acceptable failure rate line. A median of 22 procedures was required to achieve an 80% orotracheal intubations success rate. Conclusion. At least 22 procedures were required to reach an 80% success rate for orotracheal intubation using Macintosh laryngoscope in nonexperienced nurse anesthetist trainees.